Model Penyelenggaraan Program Madrasah Aliyah Negeri Insan Cendekia (MAN IC) Pekalongan Jawa Tengah - Iyoh Mastiyah Mastiyah; Elis Lisyawati (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
This paper is presented from the results of research that reveals the implementation of the program for the implementation of Madrasah Aliyah Negeri Insan Cendekia Pekalongan (MAN ICP) in terms of context, input, process and product/output aspects. This research uses qualitative methods with data collection techniques through in-depth interviews, documentation studies and observations. The findings of the study indicate that the implementation of the MAN ICP program in its implementation has referred to the guidelines for the implementation of MAN IC set by the Directorate of Islamic Education in 2013. This is reflected in the history, location and foundation of the establishment of MAN ICP, recruitment of students, teachers, employees, curriculum (input ), the implementation process and the implementation process including learning until the output targets set by MAN ICP refer to the standard guidelines made by the Directorate of Education. The implementation of the program is supported by a conducive learning environment and complete facilities as well as high integrity of educators plus governance management is open and democratic, making the learning process run effectively. So that the output of MAN ICP managed to achieve high achievements, shifting the position of Madrasah Aliyah (MA) and other high schools (SMA) in Central Java